NOEMA spatially resolved view of the multiphase outflow in IRAS17020+4544: a shocked wind in action? - Longinotti Anna Lia; Salomé Q.; Feruglio C.; Krongold Y.; García-Burillo S.; Giroletti M.; Panessa F.; Stanghellini C.; Vega O.; Patiño-Álvarez V.M.; Chavushyan V.; Elías-Chavez M.; et al. (OXFORD UNIV PRESS, 2025)
The Narrow Line Seyfert 1 Galaxy IRAS17020+4544 is one of the few active galactic nuclei (AGNs) where a galaxy-scale energy-conserving outflow was revealed. This paper reports on NOEMA observations addressed to constrain the spatial scale of the CO emission in outflow. The molecular outflowing gas is resolved in five components tracing approaching and receding gas, all located at a distance of 2–3 kpc on the west and east sides of the active nucleus. This high-velocity gas (up to vout = ±1900 km s−1) is not coincident with the rotation pattern of the CO gas in the host galaxy disc. The estimated mass outflow rate shows that with a global mass output of M˙H2 = 139±20 M⊙ yr−1, this powerful galaxy-scale outflow is consistent with the wind conserving its energy, and with a momentum rate boost of a factor of ∼30 compared to the momentum rate of the nuclear X-ray wind. Preliminary results from ancillary X-ray (Chandra) and radio images (e-MERLIN) are reported. While the nature of the radio source is not conclusive, the Chandra image may tentatively trace extended emission, as expected by an expanding bubble of hot X-ray gas. The outcome of the NOEMA analysis and of the past and ongoing publications dedicated to the description of the outflow multiband phenomenology in IRAS17020+4544 concur to provide compelling reasons to postulate that an outflow shocking with the galaxy interstellar medium is driving the multiphase wind in this peculiar AGN.